2022
DOI: 10.1108/ajar-05-2022-0144
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Covid-19 on the capital structure in emerging economies: evidence from India

Abstract: PurposeCapital structure is an important corporate financing decision, particularly for companies in emerging economies. This paper attempts to understand whether the pandemic had any significant impact on the capital structure of companies in emerging economies. India being a prominent emerging economy is an ideal candidate for the analysis.Design/methodology/approachThe study utilizes three leverage ratios in an extended market index, BSE500, for the period 2015–2021. The ratios considered are short-term lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 66 publications
(101 reference statements)
2
13
1
Order By: Relevance
“…ROE showed an increment during the pandemic as a result of the increase in DTA and LDTA, which shrank the equity portion and caused ROE to improve. The DTA and LTDA showed an increment during the pandemic, which was in contrast to the studies done by Mohd Azhari et al ( 2022) and Prakash et al (2022), where they found firms decreased their debts during the pandemic period. DTA was seen to slightly increase from 20.12% to 20.2%, whereas LTDA increased from 0.09% to 0.10%.…”
Section: Descriptive Analysiscontrasting
confidence: 96%
See 1 more Smart Citation
“…ROE showed an increment during the pandemic as a result of the increase in DTA and LDTA, which shrank the equity portion and caused ROE to improve. The DTA and LTDA showed an increment during the pandemic, which was in contrast to the studies done by Mohd Azhari et al ( 2022) and Prakash et al (2022), where they found firms decreased their debts during the pandemic period. DTA was seen to slightly increase from 20.12% to 20.2%, whereas LTDA increased from 0.09% to 0.10%.…”
Section: Descriptive Analysiscontrasting
confidence: 96%
“…This is supported by Mohd Azhari et al ( 2022), who found the presence of the pecking order theory before and during the pandemic. The same study in India also found the presence of the pecking order theory during the pandemic (Prakash et al, 2022).…”
Section: Hypotheses Developmentmentioning
confidence: 57%
“…Regarding the COVID-19, extensive research has been conducted to understand how the COVID-19 pandemic has influenced the financial structures of companies across various industries and regions. These studies have shed light on the intricate relationship between external shocks like a global pandemic and a company's capital structure choices (Prakash et al 2023;Faturohman and Noviandy 2022;Nguyen et al 2023;Vo et al 2022;Haque and Varghese 2023;Gopalakrishnan et al 2022). In this discussion, we explore several key studies that have examined the impact of COVID-19 on the capital structures of firms in different sectors and geographical locations.…”
Section: Covid-19 and Capital Structurementioning
confidence: 99%
“…These findings underscore the importance of understanding how external shocks influence financial decisions. Meanwhile, Faturohman and Noviandy (2022), Prakash et al (2023), and Vo et al (2022) showed the intricacies of capital structure adjustments in the midst of a pandemic. However, studies of the broader impact of the COVID-19 pandemic, affecting various industries, market types, and global regions, have not yet been studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation